Phytochemical Analysis, Anticancer And Antiangiogenic Activities Of Barringtonia Racemosa Extracts And Its Fractions - Amran, Norliyana (2017)
Barringtonia racemosa Roxb. (Lecythidaceae) or locally known as putat sungai have been used in the treatment of cough, asthma, ulcer and diarrhea as traditional remedy. This study investigated anticancer activity of B. racemosa fruit extract, seed extract and all its fractions, in vitro. The crude extract and its potent bioactive fraction as anticancer agent were also been investigated for their antiangiogenic and antioxidant activity. The extraction of fruits and seed were carried out by maceration method and further separated into fractions by solvent-solvent partitioning starting from n-hexane, chloroform, ethyl acetate and n-butanol.